Studying the effect of Zn-substitution on the magnetic and hyperthermic properties of cobalt ferrite nanoparticles. Issue 19 (28th April 2016) - Mameli, V.; Musinu, A.; Ardu, A.; Ennas, G.; Peddis, D.; Niznansky, D.; Sangregorio, C.; Innocenti, C.; Thanh, Nguyen T. K.; Cannas, C.
Abstract : The magnetic and hyperthermic properties of Zn-substituted CoFe2 O4 nanoparticles are studied on the basis of the chemical composition by keeping unchanged other critical parameters. Abstract : The possibility to finely control nanostructured cubic ferrites (M II Fe2 O4 ) paves the way to design materials with the desired magnetic properties for specific applications. However, the strict and complex interrelation among the chemical composition, size, polydispersity, shape and surface coating renders their correlation with the magnetic properties not trivial to predict. In this context, this work aims to discuss the magnetic properties and the heating abilities of Zn-substituted cobalt ferrite nanoparticles with different zinc contents (Zn x Co1− x Fe2 O4 with 0 < x < 0.6), specifically prepared with similar particle sizes (∼7 nm) and size distributions having the crystallite size (∼6 nm) and capping agent amount of 15%. All samples have high saturation magnetisation ( M s ) values at 5 K (>100 emu g −1 ). The increase in the zinc content up to x = 0.46 in the structure has resulted in an increase of the saturation magnetisation ( M s ) at 5 K. High M s values have also been revealed at room temperature (∼90 emu g −1 ) for both CoFe2 O4 and Zn0.30 Co0.70 Fe2 O4 samples and their heating ability has been tested. Despite a similar saturation magnetisation, the specific absorption rate value for the cobalt ferrite is three times higher than the Zn-substituted one. DC magnetometry results were not sufficient to justify these data, the experimental conditions of SAR and static measurements being quite different. The synergic combination of DC with AC magnetometry and 57 Fe Mössbauer spectroscopy represents a powerful tool to get new insights into the design of suitable heat mediators for magnetic fluid hyperthermia.